Bounds for Incidence Energy of Some Graphs - Weizhong Wang; Dong Yang (Journal of Applied Mathematics, 2013)
Let G be a simple graph. The incidence energy (IE for short) of G is defined as the sum of the singular values of the incidence matrix. In this paper, a new upper bound for IE of graphs in terms of the maximum degree is given. Meanwhile, bounds for IE of the line graph of a semiregular graph and the paraline graph of a regular graph are obtained.